Pengelolaan Data Publikasi Ilmiah Mahasiswa bagi Kepentingan Akreditasi Program Studi: Studi Kasus Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung - Hidayatul Fikra; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2024)
This study aims to discuss the management of student scientific publication data for accreditation purposes. This study uses a qualitative approach by applying descriptive-analytical methods. The results and discussion show that the management of student scientific publication data can be mapped into types of scientific publications, levels of scientific publications, author order, output categories, international collaborations. The conclusion of this study is that good management of student scientific publication data can support the accreditation of study programs with superior status.